2013
DOI: 10.1177/0969733013484486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of professional values of Taiwanese and United States nursing students

Abstract: Globalization is a part of modern life. Sharing a common set of professional nursing values is critical in this global environment. The purpose of this research was to examine the professional values of nursing students from two distinct cultural perspectives. Nurse educators in Taiwan partnered with nurse educators in the United States to compare professional values of their respective graduating nursing students. The American Nurses Association Code of Ethics served as the philosophical framework for this ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 15 publications
(19 reference statements)
9
55
1
3
Order By: Relevance
“…[40] Students in the oldest age group scored highest in Professionalism (19.14 ± 1.07). These findings were congruent with another study [12] depicting the age of the student had some implications for the responses given. Older participants responded more positively to items of Trust while on the other hand, scoring lowest on four of five items in Activism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[40] Students in the oldest age group scored highest in Professionalism (19.14 ± 1.07). These findings were congruent with another study [12] depicting the age of the student had some implications for the responses given. Older participants responded more positively to items of Trust while on the other hand, scoring lowest on four of five items in Activism.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to a comparative study in the United States of America and Taiwan where culture was identified as a determinant in the value priority and some items were rated more highly than others. [12] New graduates, graduate students as well as seasoned nursing professionals were not included in this study and may have been able to highlight a different perspective on media reports [1,2,25,26] on the professional values of nurses in Jamaica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Alfred ve ark.nın Tayvanlı ve Amerikalı hemşirelik öğrenci-leri ile yaptıkları çalışmada Tayvanlı öğrencilerin hemşirelik profesyonel değerler ölçeği puan ortalaması 104.27±16.81, Amerikalı olanların ise 106.16±12.93 olduğu belirlenmiştir. [25] Literatürde kültürün profesyonel değerlerin gelişiminde etkili bir faktör olduğu belirtilmektedir. [14] Çalışmamızda hemşirelerin cinsiyet, yaş, medeni durum, eğitim durumu ve iş deneyimi gibi faktörlerin profesyonel değerleri etkilemediği saptanmıştır.…”
Section: Discussionunclassified
“…In a study, Alfred et al (2011) compared Taiwanese and American nursing students in their attitudes toward professional values:Taiwanese students were found to consider the following caring-related factors asthe most important indexes of caring: keeping patients' secrets confidential, respecting patients' privacyand observing the principles of honesty and respect for others 18 . The results of Alfred's study are consistent with the findings of the present study where the subjects were found to consider the indexes of trust as very important.…”
mentioning
confidence: 99%